2013
DOI: 10.1186/ar4224
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 mediates local degradation and remodeling of collagen by annulus fibrosus cells of the intervertebral disc

Abstract: IntroductionDegeneration of the intervertebral disc (IVD) is characterized by marked degradation and restructuring of the annulus fibrosus (AF). Although several matrix metalloproteinases (MMPs) have been found to be more prevalent in degenerate discs, their coordination and function within the context of the disease process are still not well understood. In this study, we sought to determine whether MMP-2 is associated with degenerative changes in the AF and to identify the manner by which AF cells use MMP-2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…This miRNA was observed to be overexpressed in HBx-transfected HCC cells and HepG2 cells that constitutively replicate HBV, as well as in p21-HBx transgenic mice, and such up-regulation favored migration of HepG2 cells. In the same study, miR-29a was shown to target PTEN mRNA, thus reducing PTEN levels and favoring the activation AKT and MMP2 proteins, 110 which are involved in cell proliferation 111 and degradation of extracellular matrix, 112 respectively. Regarding telomerase modulation, there is evidence supporting that PTEN inhibits telomerase activity by reducing TERT mRNA levels, 113 while AKT up-regulates telomerase by phosphorylation of the TERT subunit.…”
Section: Non-coding Rnas In Telomerase Regulation By Oncogenic Virusesmentioning
confidence: 99%
“…This miRNA was observed to be overexpressed in HBx-transfected HCC cells and HepG2 cells that constitutively replicate HBV, as well as in p21-HBx transgenic mice, and such up-regulation favored migration of HepG2 cells. In the same study, miR-29a was shown to target PTEN mRNA, thus reducing PTEN levels and favoring the activation AKT and MMP2 proteins, 110 which are involved in cell proliferation 111 and degradation of extracellular matrix, 112 respectively. Regarding telomerase modulation, there is evidence supporting that PTEN inhibits telomerase activity by reducing TERT mRNA levels, 113 while AKT up-regulates telomerase by phosphorylation of the TERT subunit.…”
Section: Non-coding Rnas In Telomerase Regulation By Oncogenic Virusesmentioning
confidence: 99%
“…In the AF, matrix changes are accelerated with increase in age, which is thought to be a result of enhanced catabolic processing of the ECM (Akeda et al, 2007;Salo et al, 2008). While MMP-2 generally exists in an inactive pro-enzymatic form, it was observed that mechanical stress could induce MMP-2 activation (MacLean et al, 2008;Rastogi et al, 2013). Since mechanical stress is a major risk factor for the development of CDH, we hypothesized that MMP expression may be associated with the occurrence of CDH.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-2 was demonstrated to play an important part in degenerative disc disease as it interferes with the activity of AF cells (Rastogi et al, 2013). Particularly, the knockdown of MMP-2 in AF cells leads to a significantly decreased ability to reorganize and contract collagen gels (Rastogi et al, 2013). IVD tissue structure is thought to be mainly composed of collagens and proteoglycans (Kozaci et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations